- Vasculo-lymphatic neoplastic infiltration as a relevant factor in the treatment strategy and prognosis of breast cancer - Chiaffitelli, César; Vieira, Claudio; Catud, Hugo (Cirugía del Uruguay, 1997)
Vasculo-lymphatic infiltration is considered a sign of bad prognosis far malignant breast tumors.